2016
DOI: 10.1002/ecs2.1400
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of a tropical sport fish population to a severe cold event varies across five estuaries in southern Florida

Abstract: Abstract. For species that are closely managed, understanding population resilience to environmental and anthropogenic disturbances (i.e., recovery trajectories across broad spatial areas) can guide which suite of management actions are available to mitigate any impacts. During January 2010, an extreme cold event in south Florida caused widespread mortality of common snook, Centropomus undecimalis, a popular sport fish. Interpretation of trends using fishery-independent monitoring data in five south Florida es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 41 publications
0
68
0
Order By: Relevance
“…Without a long-term data set using Z-traps, it is difficult to say if the greater abundances of H. bivittatum, H. aurolineatum, and the smaller size classes of O. chrysurus and H. plumierii during fall 2009 were unusual. Differences in fish community structure between fall 2009 and spring 2010 could have been related to an extreme cold event during the winter of 2010 that caused massive mortality of patch reefs in the Florida Keys and subtropical fish species in various regions of Florida (Colella et al 2012, Stevens et al 2016). An additional possibility is that 2009 was an exceptionally good recruitment year, especially for the summer-spawning O.…”
Section: Discussionmentioning
confidence: 99%
“…Without a long-term data set using Z-traps, it is difficult to say if the greater abundances of H. bivittatum, H. aurolineatum, and the smaller size classes of O. chrysurus and H. plumierii during fall 2009 were unusual. Differences in fish community structure between fall 2009 and spring 2010 could have been related to an extreme cold event during the winter of 2010 that caused massive mortality of patch reefs in the Florida Keys and subtropical fish species in various regions of Florida (Colella et al 2012, Stevens et al 2016). An additional possibility is that 2009 was an exceptionally good recruitment year, especially for the summer-spawning O.…”
Section: Discussionmentioning
confidence: 99%
“…Rehage et al (2016) attribute this spatial variation in resilience to differences in distance to warm water source populations. Likewise, Stevens et al (2016) found that following the 2010 cold spell in Florida, resistance of a tropical estuarine piscivore were similar across three of four estuaries but resilience varied, possibly an effect related to inter-estuary differences in geophysical structuring that may influence reproduction, recruitment, and juvenile survival. Thus, landscape features are an important consideration since they can influence both resistance and resilience.…”
Section: Effects Of Landscape Features On Subtropical Community Resismentioning
confidence: 96%
“…In both Florida and China, mortality of tropical species was observed from latitudes 19°N, and 29°N, to latitudes of 24°N and 28°N, respectively (Chen et al 2016;Stevens et al, 2016, Kemp et al 2016. Despite the large footprint of the area affected by extreme cold spells, tropical species and sub-tropical community resistance and resilience vary across space.…”
Section: Effects Of Landscape Features On Subtropical Community Resismentioning
confidence: 99%
See 2 more Smart Citations